Foresight Study on Drone Adoption in Malaysia’s Agriculture Sector - Lok, Jiunn Heng; Mohd Nor, Norasmiha; Sabtu, Hilyati (Research in Management of Technology and Business, 2025)
The drone is one of the technologies that is applied by the majority of the sector in the country, for the purpose to automate the daily operations of the sector, reduce the burden of employees, and minimize the cost in the sector. Currently, drones have been adopted in the agriculture sector. The purpose of the study is to identify the issues, challenges, and trends of drones in the agriculture sector, to study the key drivers of drones in the agriculture sector, and to analyze the future image of drones in the agriculture sector. There are 384 respondents selected, in which around the stakeholders in the agriculture sector. The research applied the quantitative methods, in which this research is proceeding the foresight instruments. For instance, the STEEPV analysis and SPSS analysis. STEEPV analysis is using to identify the issues, challenges, and trends of drones in the agriculture sector, while the SPSS analysis is applying in the research, for purpose to display the result of the key drivers of drones in the agriculture sector in the second phase of the research with impact-uncertainty analysis. This research is evaluating and identifying 10 merged key drivers. This study also used the impact-uncertainty analysis to determine the future image of drones in the agriculture sector.